Understanding Pancasila Values Among Young People in the Digital Technology Era: A Case Study in Duman Village, Lingsar District, West Lombok Regency - Baiq Syakila Dwi Satria; Ferlina Jayanti; Haerul Alfin; Fiqri’ah; Hani Amelia Putri; Igatun Haniah; Muh. Zubair (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to examine the understanding of Pancasila values among young people in the digital technology era, focusing on a case study in Duman Village, Lingsar District, West Lombok Regency. The method used is qualitative descriptive research with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the level of understanding of young people towards Pancasila values tends to decline due to the influence of digital technology and global culture. However, digital media also provides opportunities to improve understanding of Pancasila values through creative content such as educational videos and social campaigns. The main challenges include the influence of individualistic culture, the spread of hoaxes, and lack of supervision in the use of social media. However, respondents showed awareness of the importance of implementing Pancasila values, such as mutual cooperation, tolerance, and social justice. This study emphasizes the importance of a comprehensive strategy that integrates digital technology to effectively convey Pancasila values to the younger generation as an effort to build national character in the digital era.